Design of an 8-Story Reinforced Concrete Hotel Building Using a Moment-Resisting Frame System at Sepakat II Street in Pontianak City - Damara, Rieky; Sasongko, Hartanto Wahyu; Rahmasari, Puspita; Anggraini, Irene (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
Pontianak City has experienced a steady increase in tourist arrivals, which has resulted in a higher demand for temporary accommodation facilities. In response to this development, this study presents the structural design of an eight-story reinforced concrete hotel building located on Sepakat II Street in Pontianak City. The structure is designed using an Intermediate Moment-Resisting Frame (IMRF) system to ensure adequate performance under seismic loading conditions. The structural design process was carried out in accordance with the applicable Indonesian National Standards (SNI). Structural analysis was conducted using ETABS software to evaluate the building’s behavior under gravity and earthquake loads, while technical drawings were prepared using AutoCAD and SketchUp. The building utilizes concrete with a compressive strength of f’c = 30 MPa and reinforcing steel with a yield strength of fy = 420 MPa. The seismic performance of the structure was evaluated through several parameters, including mass participation ratios, inter story drift limits, natural period verification, and P-Delta effects. The analysis results show that the structural system satisfies all required performance criteria, indicating that the building is capable of resisting seismic forces safely and efficiently. The slab system consists of D10 main reinforcement bars and Ø8 shrinkage reinforcement bars, with slab thicknesses of 150 mm for the roof, 130 mm for typical floors (Levels 1–8), and 160 mm for stair landings. The primary beams (B1) have cross-sectional dimensions of 300 × 600 mm and are reinforced with D19 longitudinal bars, D13 shear reinforcement, and D19 torsional reinforcement. Secondary beams (B2) measure 200 × 400 mm and use D16 longitudinal bars, D13 shear reinforcement, and D16 torsional reinforcement. Columns have a uniform cross-section of 700 × 700 mm and are reinforced with 20D22 longitudinal bars and D13 transverse reinforcement. The foundation system consists of three types of pile foundations using 200 × 200 mm precast concrete piles with reinforced pile caps designed to accommodate varying structural loads.